Development of Web-based Network Traffic Analysis and Monitoring System - Mohd Razali, Nur Misha Nabila (Journal of Methodical Computing and Communications, 2025)
The usage of the network is undoubtedly enormous especially when almost everything is being digitalized and in need of the Internet nowadays. This actually causes a lot of issues that happen on the network, such as the connection being slow, the network security being vulnerable to attacks, and more, which eventually require the need to monitor the network traffic. So, network traffic monitoring is a process of managing, analyzing, and observing the network traffic to find the irregularity that affects the network. It can be considered vital to analyze the network traffic to ensure a smooth operation. However, although there are many existing tools that are available to analyze and monitor the network, they are found to be quite difficult to use due to their user interface. Thus, the system presented in this paper is able to capture the network traffic, analyze it, and visualize the information being retrieved into a user-friendly and easy-to-understand interface.